2012
DOI: 10.1016/j.jalz.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of molecular imaging on the diagnostic process in a memory clinic

Abstract: In a memory clinic setting, combined [(11)C]PIB and [(18)F]FDG PET are of additional value on top of the standard diagnostic work-up, especially when prior diagnostic confidence is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
155
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 36 publications
17
155
0
8
Order By: Relevance
“…Diagnosis remained unchanged in 96% after PET over the next 2 years. 15 In seven patients with MCI and positive amyloid deposition on 11 C-PIB PET, six progressed to AD during follow-up (5 had AD pattern of hypometabolism on 18 F-FDG PET). 15 In a retrospective study of 94 patients with MCI or dementia, Laforce et al 16 showed that 18 F-FDG PET brain scan led to a change in diagnosis in 29% of patients, and reduced the frequency of atypical or unclear diagnoses from 39.4% to 16%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Diagnosis remained unchanged in 96% after PET over the next 2 years. 15 In seven patients with MCI and positive amyloid deposition on 11 C-PIB PET, six progressed to AD during follow-up (5 had AD pattern of hypometabolism on 18 F-FDG PET). 15 In a retrospective study of 94 patients with MCI or dementia, Laforce et al 16 showed that 18 F-FDG PET brain scan led to a change in diagnosis in 29% of patients, and reduced the frequency of atypical or unclear diagnoses from 39.4% to 16%.…”
Section: Discussionmentioning
confidence: 95%
“…The latter are referral centres, and often encounter patients with complicated diagnostic issues. Ossenkoppele et al 15 reported a cohort of 145 patients who underwent 18 F-FDG and 11 C-PIB PET after clinical assessment. Change in clinical diagnosis was required in 23% with the diagnostic confidence increased from a mean of 71% to 87%.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of bvFTD remains difficult, with patients being erroneously diagnosed with Alzheimer's disease (AD) or psychiatric disorders 5, 6, 7. A large body of work has demonstrated that brain imaging, in particular structural magnetic resonance imaging (MRI) and functional imaging of cerebral blood flow (CBF) with SPECT or cerebral metabolic rate of glucose (CMRgl) with fluorodeoxyglucose (FDG) positron emission tomography (PET), can improve the accuracy of differential diagnosis in bvFTD 8, 9, 10, 11, 12, 13, 14, 15, 16, 17. These findings led the Center for Medicare and Medicaid Services (CMS) to approve FDG‐PET as a diagnostic test for differentiating bvFTD from AD (https://www.cms.gov/medicare-coverage-database/details/ncd-details.aspx?NCDId=288&ncdver=3&bc=BAABAAAAAAAA&).…”
Section: Introductionmentioning
confidence: 99%
“…However, both these values were higher than 80 % in about half of the studies included [15][16][17][18][19][20], an accuracy that compares better with previous studies in which confirmation of underlying neurodegenerative pathology was obtained at autopsy. In the latter case, [ 18 F]FDG PET identified patients with AD with a sensitivity of 94 % and a specificity of 73 % [21].…”
Section: Results Of the Cochrane Reviewmentioning
confidence: 84%